Hay-based activated biochars obtained using two different heating methods as effective low-cost sorbents: Solid surface characteristics, adsorptive properties and aggregation in the mixed Cu(II)/PAM system. (July 2020) - Szewczuk-Karpisz, Katarzyna; Nowicki, Piotr; Sokołowska, Zofia; Pietrzak, Robert
Abstract: The main aim of the study was to compare the sorption capacity of hay-based activated biochars, obtained using conventional and microwave furnance, relative to copper(II) ions and ionic polyacrylamides (PAM). Surface properties of the solids were characterized by, inter alia, N2 adsorption/desorption isotherm method, whereas their tendency to aggregation was established turbidimetrically. Adsorption capacity of biochars were performed in the simple and mixed Cu(II)/PAM systems, i.e. the examined suspensions contained one or two adsorbates at the same time. The results indicated that biochar prepared in microwave furnance was characterized by larger micropore area and, as a result, it had higher adsorption capacity relative to Cu(II) ions. At pH 6, when the initial Cu(II) concentration equaled 100 mg/L, the biochar obtained by microwave heating adsorbed 81.5% of Cu(II) ions, whereas the one obtained by conventional heating – 51.6%. Due to high molecular weight, the PAM macromolecules could not penetrate the biochar micropores and thus the polymer adsorbed amounts were similar for both materials. For initial polymer concentration equal to 100 mg/L, the solids adsorbed 65–66.2% of cationic PAM containing 25% of quaternary amine groups. In the mixed system of anionic polyacrylamide and Cu(II) ions, the formation of Cu(II)-PAM complexes occurred, which favored both heavy metal and polymer adsorption on the solid surface. On the other hand, cationic polyacrylamide and heavy metal ions made the contact with the solid difficult for each other. What is more, ionic polyacrylamide and copper(II) ions stimulated the biochar aggregation due to surface charge neutralization and flocculation. Graphical abstract: Image 1 Highlights: Microwave heating contributes to larger micropore area in activated biochar (AB). AB obtained in microwave furnace is more effective adsorbent for copper(II) ions. Anionic polyacrylamide favours Cu adsorption due to Cu-PAM complex formation. Cu(II) ions increase the adsorbed amount of anionic polyacrylamide on ABs. Polyacrylamide and Cu(II) ions stimulate the activated biochar aggregation.